Zuhd as an Ethical Critique of Digital Hedonism: A Literature-Based Study from the Perspective of Islamic Economic Ethics - Maula Nasrifah; Sirajul Arifin (Muhasabatuna : Jurnal Akuntansi Syariah, 2025)
Digital hedonism, which has intensified through social media, platform-based economies, and instant consumption culture, has fostered behavioral patterns oriented toward pleasure-seeking, excessive self-presentation, and self-commodification. These developments have generated significant ethical tensions in the consumption practices of Muslim communities. This article examines the concept of zuhd as an ethical critique of digital hedonism using a qualitative library research approach. Data were drawn from classical and contemporary Islamic literature as well as empirical studies on digital consumption and Islamic economic ethics. The analysis reveals that zuhd should not be understood as hostility toward pleasure or technology, but as a value-oriented framework that regulates consumption motives in accordance with spiritual objectives (maqāṣid al-sharīʿah). In the digital context, zuhd functions as an ethical compass that mitigates consumptive pressure, strengthens self-awareness, and reorients the moral use of technology. This study offers a conceptual contribution to the development of digital consumption ethics within Islamic economic thought.